Influência da gestão de riscos sobre a eficiência da gestão acadêmica nas universidades federais brasileiras - Nunes, Naiara Taise Sousa (2021)
The expansion of public higher education in the past few decades has been revealed by the foundation of new universities, as well as by the increasing number of university places. This growth turns the university management more complex, as it renders the confront of more significant and more diverse risks. In this context, having a control and risk management system is critical in reducing uncertainties pertinent to its activities and achieving these institutions’ goals. Under this perspective, the general objective of this study consisted in investigating the influence of risk management index in the Brazilian universities, according to Brazil’s Federal Court of Accounts (TCU), in respect of the relative efficiency of academic management of these institutions, considering the external control management index of TCU and social control index derived of national and international rankings. Therefore, this descriptive, quantitative and documental study carried out data envelopment analysis of 63 federal universities in order to measure their relative efficiency of academic management in the accounting period of 2018. Subsequently, a linear regression test was conducted in contemplation of the general objective. The results indicate that 10 Brazilian federal institutions of higher education (FIGE) reached the efficiency frontier, and the national average score was 0,8165. UFMG, UFPA, and UFOPA were universities that mainly served as benchmarks to other universities. The results of the regression testing allowed to identify a significant positive degree of focus’ influence on the efficiency of FIGE’s post-graduation programs; a significant negative influence of IQCD (teacher qualification variable) only for universities with higher efficiency scores; regarding the age, significant positive influence to FIGE of the first decile and significant negative to the last decile FIGE. Contradicting the literature of the theoretical reference used, it was not possible to assert that the risk management index of the FIGE measured by TCU impacts the relative efficiency of academic management in federal universities.